Comment on "(Au–Ag)144(SR)60 alloy nanomolecules" by C. Kumara and A. Dass, Nanoscale, 2011, 3, 3064. Issue 17 (2nd May 2014) - Barcaro, Giovanni; Sementa, Luca; Fortunelli, Alessandro; Stener, Mauro
Abstract : Ligands quench alloying effects in thiolated clusters. Abstract : A recent paper in this journal reported the synthesis and characterization via electrospray ionization mass spectroscopy and UV-vis spectroscopy of (Au–Ag)144 (SR)60 alloy nanomolecules with different compositions, ranging from 1 : 0 to 1 : 0.75 Au : Ag ratios. The UV-vis spectra of such systems were found to exhibit absorption peaks at 310 nm, 425 nm and 560 nm, interpreted as reminiscent of the silver surface plasmon resonance band due to simple atomic replacement of Au by Ag atoms in a fixed structural framework. On the basis of a comparison of experimentally observed and theoretically simulated optical absorption spectra, we conclude that the experimental situation must be more complicated, and that further work is needed to achieve atomistic insight into these fascinating systems.